2020
DOI: 10.1126/sciadv.aaz0742
|View full text |Cite
|
Sign up to set email alerts
|

Proximo-distal positional information encoded by an Fgf-regulated gradient of homeodomain transcription factors in the vertebrate limb

Abstract: The positional information theory proposes that a coordinate system provides information to embryonic cells about their position and orientation along a patterning axis. Cells interpret this information to produce the appropriate pattern. During development, morphogens and interpreter transcription factors provide this information. We report a gradient of Meis homeodomain transcription factors along the mouse limb bud proximo-distal (PD) axis antiparallel to and shaped by the inhibitory action of distal fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 53 publications
5
79
0
Order By: Relevance
“…Studies in zebrafish (Choe et al, 2014) and mouse (Amin et al, 2015) embryos indeed showed that some of these binding sites represent Hox auto-regulatory elements active in the neural tube and Hox transcription regulation by MEIS factors has been demonstrated in neural tube patterning (Dibner et al, 2001;Vlachakis et al, 2001;Waskiewicz et al, 2001). MEIS elimination or overexpression also affects Hox gene expression during limb skeletal patterning (Delgado et al, 2020;Mercader et al, 1999;Mercader et al, 2009;Rosello-Diez et al, 2014), however, this aspect has not been studied in axial skeleton patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in zebrafish (Choe et al, 2014) and mouse (Amin et al, 2015) embryos indeed showed that some of these binding sites represent Hox auto-regulatory elements active in the neural tube and Hox transcription regulation by MEIS factors has been demonstrated in neural tube patterning (Dibner et al, 2001;Vlachakis et al, 2001;Waskiewicz et al, 2001). MEIS elimination or overexpression also affects Hox gene expression during limb skeletal patterning (Delgado et al, 2020;Mercader et al, 1999;Mercader et al, 2009;Rosello-Diez et al, 2014), however, this aspect has not been studied in axial skeleton patterning.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on the molecular mechanism of congenital limb deformity has intensified. The importance of the fibroblast growth factor family in limb development is well known, but the specific role of its various factors in the family and its mechanism of action have not been fully studied [ 22 , 23 ]. A study showed that FGF4 plays an important role in early embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proximal structures are lost in Meis1 and Meis2 mutants because of the precocious activation of the 5′-most Hox genes. However, Hoxa11 and then Hoxa13 are still progressively activated in the absence of Meis function (Delgado et al, 2020), which suggests that a timing mechanism underlies this transition (Fig. 5).…”
Section: Limb Pattern Specification Proximo-distal Specificationmentioning
confidence: 97%
“…The authors explain these results in terms of an instructive model in which the Fgf to RA ratio is interpreted into a gradient of Meis1 and Meis2 abundance that specifies proximo-distal positional values: high Meis1 and Meis2 would specify proximal positional values, low Meis1 and Meis2, intermediate positional values and absent Meis1 and Meis2, distal positional values (Fig. 5) (Delgado et al, 2020). The diminishing levels of RA, Meis1 and Meis2 would allow the progressive activation of Hoxa11 to Hoxa13.…”
Section: Limb Pattern Specification Proximo-distal Specificationmentioning
confidence: 97%
See 1 more Smart Citation